Kenyamanan Visual Melalui Pencahayaan Alami Pada Kantor (Studi Kasus Gedung Dekanat Fakultas Teknik Universitas Brawijaya Malang) - Thojib, Jusuf; Adhitama, Muhammad Satya (RUAS (Review of Urbanism and Architectural Studies), 2013)
Office as a work area requires an adequate level of comfort, so that users can carry out activities smoothly and has a good working productivity . Convenience is not only dependent on the temperature in the chamber , incoming solar radiation , air quality , and weather quality , but is also determined by the quality of the lighting. Indonesia with rich conditions year-round sunshine should put natural lighting as a priority in the design ; aside as environmental response efforts , utilization also can save energy consumption of building. research was designed to evaluate the visual comfort of the application of natural lighting in the office building, on case study Dekanat Fakultas Engineering University Brawijaya ( UB FT ) Malang. method descriptive and correlational research , seeks to combine the observations ( observations made in the form of illumination with luxmeter measurement , simulation contours of natural lighting , the identification of the elements that affect the natural lighting ) with the perception of the user to get an overview of visual comfort and design characteristics of natural lighting in buildings FT UB so as at a later stage can be given recommendations for the achievement of better visual comfortKeywords: office, visual comfort, natural lighting